EVALUASI TINGKAT KETERAMPILAN SEPAK TAKRAW PADA ATLET PPLPD ACEH TAHUN 2019 - Taufiqul Khaliq; Masri Masri (Jurnal Dedikasi Pendidikan, 2021)
During training researchers saw athletes perform service techniques that did not pass the net, imperfect recieve techniques ,weak smash techniques and not even on target often also did not pass the net, feed techniques that were not so perfect that the killer could not smash, did not dare block so that the ball entered easily. Football skills play a very important role in a match and the success of training in a training center. The purpose of the study was to find out the level of takraw football skills in PPLPD Aceh athletes in 2019. The population of this study was Pplpd Aceh athletes and the study subjects numbered 8 people with total sampling techniques. Data collection is done by takraw football skills test consisting of Service, Receive, Smash, Feed, Block. The data obtained by youth was analyzed using statistical techniques in the form of percentages and category helpers. In conclusion, the mean value of service skills is 34.87 in the "Good" category, the average value of recieve skills is 24 in the "Good" category, the average value of smash skills is 27.75 in the "Less" category, the average feeder skill value is 32.62 in the "Medium" category, the average block skill value is 18.5 in the "Medium" category. This means the service, recieve, is in a good category, while feed and block are in the Medium category, and Smash is in the category of less. This signifies the need for further improvement and coaching exercises specifically for smash skills.